Exploring the anticancer potential of Eleutherine bulbosa: A systematic network pharmacology study on lung cancer - Roihatul Mutiah; Ermin Rachmawati (Wolters Kluwer Medknow Publications, 2024)
Chemotherapy application in lung cancer patients has several side effects and shows lower effectiveness due to chemoresistance. Although Eleutherine bulbosa (Mill.) Urb. (EBE) elicit anticancer properties, yet the exact profile of its active compounds and lung cancer inhibition mechanisms were not fully understood. This study aimed to identify suggestive compounds from EBE extract and explain the molecular mechanisms of EBE against lung cancer. Identification of the compound from the EBE extract was confirmed using liquid chromatography-tandem mass spectrophotometry (LC-MS/MS). The bioavailability profile of three major metabolites was identified using absorption, distribution, metabolism, excretion, toxicity software. The anticancer molecular mechanism prediction of the drugs was ascertained by network pharmacology using Cytoscape 3.9.1 and the protein-protein interaction network technique with STRING 11.0. Interaction between resveratrol and extracellular growth factor receptor (EGFR) was analyzed using site-specific molecular docking with erlotinib as the control using PyRx Autodock Vina 9.0 and BIOVIA Discovery Studio. A total of 16 active compounds were identified from LC-MS/MS. Only resveratrol showed anticancer properties by its interaction with 13 genes and 6 signaling pathways related to lung cancer. The molecular docking result supports the network pharmacology finding. The binding affinity of resveratrol with EGFR, important receptor in lung cancer, was more negative (−6.9 kcal/mol) than erlotinib (−6.2 kcal/mol) as the control. Evidence suggested that resveratrol in EBE exhibits anticancer effects by modulating lung cancer cell proliferation and apoptosis through EGFR binding.